2017
DOI: 10.1021/acs.jmedchem.7b00699
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis and in Vivo Evaluation of Regioisomeric Analogues of the Antimalarial Arterolane

Abstract: We describe the first systematic study of antimalarial 1,2,4-trioxolanes bearing a substitution pattern regioisomeric to that of arterolane. Conformational analysis suggested that trans-3″-substituted trioxolanes would exhibit Fe(II) reactivity and antiparasitic activity similar to that achieved with canonical cis-4″ substitution. The chiral 3″ analogues were prepared as single stereoisomers and evaluated alongside their 4″ congeners against cultured malaria parasites and in a murine malaria model. As predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…It has been observed that making modifications in bond rigidity, adding different groups like amines, etc., can increase the potency against the resistant species [ 114 ]. It was also noted that changing the stereochemistry and position of different groups attached to the nucleus of drugs can enhance the antiplasmodial efficacy [ 115 ]. For example a stereoisomeric analogue ( Figure 7 c) of arterolane is more potent than the arterolane itself [ 115 ].…”
Section: Artemisinin Inspired Novel Antimalarial Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that making modifications in bond rigidity, adding different groups like amines, etc., can increase the potency against the resistant species [ 114 ]. It was also noted that changing the stereochemistry and position of different groups attached to the nucleus of drugs can enhance the antiplasmodial efficacy [ 115 ]. For example a stereoisomeric analogue ( Figure 7 c) of arterolane is more potent than the arterolane itself [ 115 ].…”
Section: Artemisinin Inspired Novel Antimalarial Compoundsmentioning
confidence: 99%
“…It was also noted that changing the stereochemistry and position of different groups attached to the nucleus of drugs can enhance the antiplasmodial efficacy [ 115 ]. For example a stereoisomeric analogue ( Figure 7 c) of arterolane is more potent than the arterolane itself [ 115 ].…”
Section: Artemisinin Inspired Novel Antimalarial Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the peroxide bond is more exposed and consequently more susceptible to premature activation (Figure 12C). 125 Heme has been reported as an alkylation target of the antimalarial 1,2,4-trioxolanes, as observed in artemisinins. The reaction of OZ277 with heme gave the covalent heme adduct 85 120,121,126 (Figure 12D).…”
Section: Mechanism Of Action Of Dispiro-124-trioxolanesmentioning
confidence: 99%
“…[6][7][8] Spurred by thesec oncerning indicators, the scientific community is actively seeking alternative treatments. In analogy to artemisinin (1), potent inhibitors containing ap harmacophoric peroxide bond have been investigated, such as artemisone( 2); [9] E209 (3); [10] artefenomel (4); [11] as well as arterolane (5) [12] and its regioisomeric analogues, including aminopiperidine 6 [13] (for structures, see SectionS1, Figure S1 in the Supporting Information). Promising efficacy was also achieved with non-endoperoxide scaffolds,i ncluding NITD609 (7), [14,15] KAF156 (8), [16][17][18][19][20] DSM265 (9), [21,22] and aminoxadiazole-based ligands (Supporting Information, Section S1, Figure S2).…”
Section: Introductionmentioning
confidence: 99%